Implementasi Manajemen Kurikulum dalam Pembiasaan Ibadah Salat Dhuha di MI Miftahul Akhlaqiyah Kota Semarang - Imelia Sahda Salsabilla; Yuda Agustian; Syaiful Bakhri (Jurnal DinamikA, 2025)
This study analyzes curriculum management in the habitualization of the dhuha prayer at MI Miftahul Akhlaqiyah in Semarang by examining the aspects of planning, implementation, supervision, and evaluation. The phenomenon in the field shows that the integration of the dhuha prayer into the curriculum has not been optimal because its practice still depends on the initiative of teachers and is not yet supported by structured regulations. This condition has implications for low consistency in implementation compared to other madrasahs that have implemented similar programs more routinely. Using a qualitative approach with case studies, data was collected through in-depth interviews, observations, and documentation involving the head of the madrasah and teachers as the main informants. The findings indicate weaknesses in supervision that have resulted in inconsistent implementation, while the evaluations that have been conducted have not led to significant policy improvements. Overall, the results of the study emphasize the importance of strengthening curriculum governance so that the habit of performing the dhuha prayer can be implemented more consistently and contribute to the formation of the religious character of students.